Simulating the effect of muscle stiffness and co-contraction on postural stability. Issue 5 (3rd September 2018) - Shabani, Mohammad; Stavness, Ian
Abstract: Posture perturbation experiments can be used to assess the biomechanical factors underlying postural stability. However, experiments are limited by participant safety, inability to measure important factors such as muscle forces and the large number of conditions to be tested. We employed forward dynamics computer simulations to mimic posture perturbation experiments to assess the effect of short-range muscle stiffness and muscle co-contraction on the postural stability of a musculoskeletal model. Two novel simulation techniques were developed: a static-optimisation formulation that uses target joint stiffness to elicit muscle co-contraction and a realisation of a short-range stiffness muscle model as a passive, pre-stressed spring that can be used in forward dynamics simulations. Our simulation results demonstrated that the realistic short-range stiffness has a large impact on postural stability as compared to traditional Hill-type muscle models that underestimate intrinsic stiffness. We also found that muscle co-contraction contributed to postural stability, but to a lesser extent than the realistic intrinsic stiffness alone. Although the present study does not consider active responses, our simulations have revealed important factors that contribute to the body's intrinsic stability and that may be helpful, in part, for compensating for diminished or delayed postural responses to maintain balance.